PENERAPAN STRATEGI PEMBELAJARAN AKTIF LEARNING START WITH QUESTIONUNTUK MENCAPAI KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN TERMOKIMIA KELAS XI IPA 6 SMA NEGERI 5 PEKANBARU: (Application of Learning Start with Question Active Learning Strategy to Achieve Student Learning outcome in Termokimia Class XI IPA 6 SMA Negeri 5 Pekanbaru) - Andri Dirgahayuning (UIR Press, 2017)
ABSTRACTImproving the quality of education in Indonesia is done continuously and up to now continueto be implemented. One effort to improve teacher quality through certificationprogram.Through this program teachers are expected to have professional skills that requireskills, skills or skills that meet certain quality standards or norms.One of the majorprofessional skills and skills that educators need to have is the ability of the field of educationand teacher training, particularly with regard to learning strategies. A teacher and lecturer isnot only required to master the field of study that will be taught only, but also must masterand be able to teach the knowledge and skills to the learners. The main problem faced incurrent chemistry learning is that students are less active in learning and this is evident fromthe lack of student participation in learning the subject matter and the high number of studentscores under the established KKM.Based on the observation of class XI IPA 6 SMA N 5Pekanbaru can be concluded that there is a gap between expectations and reality that is stillthe number of students under the KKM that has been set that is ≥ 80 for class XI IPA 6.Students' learning outcomes, especially on thermochemical subject has not reachedcompleteness . The average score of students is only 62 and has not reached completeness inschool that is ≥ 80.One of the strategies that is expected to foster student activeness inlearning is Learning Start With Question (LSQ) strategy is an active learning strategy inasking. Learning Start With Question (LSQ) learning strategy is an active type of learning bymaking students ask questions before being given explanations by teachers. This strategyemphasizes the skills of reading and questioning skills, because before students ask studentsare required to read the material to be studied first.Thus learning using LSQ strategy willmotivate students to be more active and creative in thinking so as to achieve student learningmastery. Based on the result of the research, it is found that using Learning Start WithQuestion (LSQ) strategy can improve students' learning outcomes as evidenced by the resultsof cycle I and cycle II respectively as follows 72.22% and 61.11%..